Antibacterial effects of silver diamine fluoride with and without potassium iodide against Streptococcus mutans - Carlos Alonso Alvarez-Marín; Norma Leticia Robles-Bermeo; Wael Hegazy Hassan Moustafa; Carlo Eduardo Medina-Solís (Wolters Kluwer Medknow Publications, 2024)
Introduction: Silver diamine fluoride (SDF) is a topical treatment for carious lesions and a primary preventative for newly exposed high-risk surfaces such as fissures and roots in the first molars. Using potassium iodide (KI) after applying SDF has been recommended as a way of reducing the severity of black staining, as well as preserving its antibacterial effect useful in deep caries. Objective: The objective of this research was to compare the antibacterial effect of SDF, with and without KI, on Streptococcus mutans (S. mutans) and dental biofilm. Methods: The antibacterial effects of SDF, KI, and the combination of both were measured using three different techniques (inhibition halo, minimum inhibitory effect [MIE], and colony-forming unit [CFU], testing). Results: The results were then subjected to statistical analysis. Analyzed by means of the Kruskal-Wallis statistical test, the inhibition halos yielded a value of P = 0.3309. Using the MIE test, only the SDF treatment produced an antibacterial effect, at 10%, compared to the KI group, with P = 0.001. Finally, the CFU test revealed a total absence of colonies for all three reagents. All three substances analyzed achieved total inhibition of S. mutans. SDF is effective even in its minimal commercial concentration. Its antibacterial capacity decreases with the addition of KI. Conclusions: The three substances analyzed at their maximum concentrations exhibited an antibacterial effect against S. mutans, resulting in total inhibition.